Isoquinoline‐1‐Carboxylate as a Traceless Leaving Group for Chelation‐Assisted Glycosylation under Mild and Neutral Reaction Conditions. Issue 49 (3rd November 2017) - Wang, Hao‐Yuan; Simmons, Christopher J.; Blaszczyk, Stephanie A.; Balzer, Paul G.; Luo, Renshi; Duan, Xiyan; Tang, Weiping
Abstract: Glycosyl isoquinoline‐1‐carboxylate was developed as a novel benchtop stable and readily available glycosyl donor. The glycosylation reaction was promoted by the inexpensive Cu(OTf)2 salt under mild reaction conditions. The copper isoquinoline‐1‐carboxylate salt was precipitated from the solution and thus rendered a traceless leaving group. Surprisingly, the proton from the acceptor was absorbed by the precipitated metal complex and the reaction mixture remained at neutral pH. The copper‐promoted glycosylation was also proven to be completely orthogonal to the gold‐promoted glycosylation, and an iterative synthesis of oligosaccharides from benchtop stable anomeric ester building blocks becomes possible under mild reaction conditions. Abstract : Generous donor : A new glycosyl ester donor was developed. It is readily available, benchtop stable, reactive upon chelation to inexpensive copper salts under mild and neutral reaction conditions, orthogonal to other glycosyl esters, serves as a traceless leaving group, and facilitates a broad substrate scope. Tf=trifluoromethanesulfonyl.